Understanding flood and drought extremes under a changing climate in the Blue Nile Basin: A review - Demelash Ademe Malede; Vetrimurugan Elumalai; Tesfa Gebrie Andualem; Yilkal Gebeyehu Mekonnen; Mesenbet Yibeltal; Girum Getachew Demeke; Tena Alamirew; Shimelash Molla Kassaye; Yonas Gebreslasie Hagos; Anmut Enawgaw Kassie; Mulatu Kassa; Gizachew Sewagegn Berihun; et al. (Environmental and Sustainability Indicators)
Extreme flood and drought events arise from temporal and spatial variations in the Earth's water cycle, significantly affecting water resources and the environment. This review aimed to evaluate the effects of climate variabilities on extreme flood and drought events within the Blue Nile Basin. A systematic literature review and content analysis were conducted to understand the hydrological dynamics of floods and droughts. A Scopus database was used to find relevant literature review articles related to flood and drought extreme events using search terms queries. The findings suggest that rising temperatures and fluctuating precipitation patterns are leading to more frequent and severe floods and droughts. Future projections also suggest increased drought severity in most basin areas, coupled with more frequent floods. Fluctuations between dry and wet conditions have intensified these extremes. While insufficient rainfall triggers droughts, excessive and concentrated rainfall contributes to floods. The wet projection shows more frequent floods, while the dry projection indicates severe droughts throughout most of the basin. This review provides a valuable starting point for further action towards a more climate-resilient and water-secure for sustainable environmental development and management over the basin.